Analisis Penerapan Standar Operasional Prosedur (SOP) Pada Departemen Inventory PT. Rimex International Indonesia Balikpapan - Isti Prabawani; Yizrel Junus Kende; Ratna Ratna (Lembaga Pengembangan Kinerja Dosen, 2023)
SOPs can be defined as documents that describe operational activities carried out daily, with the aim that the work is carried out correctly, precisely, and consistently, to produce products according to predetermined standards” (Tathagati, 2014). The existence of SOP will help the company to achieve company goals. To achieve company goals, the company provides a design in the form of an SOP that will guide employees in carrying out their duties and minimize errors in carrying out the responsibilities of each employee. This study aims to determine the application of standard operating procedures (SOP) in the Inventory Department at PT RIMEX International Indonesia Balikpapan. This type of research is qualitative concerning the 7 main points in the SOP which include efficiency, consistency, minimizing errors, problem-solving, and defense boundaries. There are 3 research informants: One supervisor, one Quality Control, and 1 Warehouseman. Data collection techniques through interviews. The results of the analysis show that Inventory Department employees have implemented the SOP made by the company. The problem found is that there are differences in goods between the recording of goods in the company's recording system and the physical goods between the recording of goods in the company's recording system and the physical goods in the warehouse, such as how many items are left, abandoned and how many items are left in the warehouse.